Edible Insects as Innovative Foods: Nutritional, Functional and Acceptability Assessments II - Meyer-Rochow, Victor Benno; Jung, Chuleui (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
It was first suggested nearly 50 years ago by Meyer-Rochow in Australia that the use of insects as food and feed sources could ease the problem of global food shortages, and that the WHO and the FAO should support the promotion of insects as a food item, especially in countries with a long tradition of entomophagy. However, food shortages in some parts of the world are only one aspect to consider; overeating and obesity in other parts of the world are another aspect. An increased use of edible insects might well be able to assist in overcoming, at least to some extent, both of these problems. This Special Issue of Foods represents Volume 2 of the topic "Edible Insects as Innovative Foods: Nutritional, Functional and Acceptability Assessments". Some of the 20 contributions by scientists from 13 different countries deal with hitherto unreported food insects, and others explore the effects that a diet containing insects or insect products can have on the gut microbiota of the consumer, whether human or non-human. Food safety questions are not ignored, and questions related to the chemical composition of food insects, their content in terms of nutrients and antinutrients, and their acceptability by consumers are additional topics that the articles in this book explore. Altogether, this reprint provides convincing reasons for the advantages to health and the environment that a greater use of insects as food and feed would present, and ends with the slogans "Forget about the pork and put a cricket on your fork!" and "Mealworms and spaghetti is food that makes you happy!".